2015
DOI: 10.3109/14992027.2014.943845
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wideband frequency responses and non-linear frequency compression for children with mild to moderate high-frequency hearing loss

Abstract: Children with mild to moderate hearing loss have good access to high-frequency phonemes presented at fixed levels (e.g. 50 to 60 dBA) with both wideband and NLFC technology. Similarly, sentence recognition in noise was similar with wideband and NLFC. Adaptive test procedures that probe performance at lower input levels showed small but significant improvements in the detection and recognition of the phonemes /s/ and /sh/ with NLFC condition when compared to the NLFC Off and wideband conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…This expectation was partially supported by the data because 33%-50% improvements in consonant recognition for the /s/ and /z/ from the high-frequency stimulus set and for isolated tokens from the VCV stimulus set (mainly, fricative and stop consonants) occurred with NFC settings that were the most detrimental to low-frequency dominated vowels (low SF, medium to high CR). These results are consistent with several other studies on children and adults that found that improvements with NFC were primarily limited to medial or final /s/ and /z/ in quiet or in noise, especially using tests of discrimination threshold and plural detection (e.g., Simpson et al, 2005;Wolfe et al, 2010;Wolfe et al, 2011;Wolfe et al, 2015;Glista et al, 2009;Glista et al, 2012;Alexander et al, 2014;Hopkins et al, 2014;Zhang et al, 2014;Picou et al, 2015;Ellis and Munro, 2015). The difference in outcomes for the final vs medial /s/ in this study (VCV context vs /iC/ context) may be attributed to nonspectral cues that can help distinguish it from the final / Ð /, such as duration and intensity (e.g., Jongman et al, 2000), with the latter being longer and louder.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This expectation was partially supported by the data because 33%-50% improvements in consonant recognition for the /s/ and /z/ from the high-frequency stimulus set and for isolated tokens from the VCV stimulus set (mainly, fricative and stop consonants) occurred with NFC settings that were the most detrimental to low-frequency dominated vowels (low SF, medium to high CR). These results are consistent with several other studies on children and adults that found that improvements with NFC were primarily limited to medial or final /s/ and /z/ in quiet or in noise, especially using tests of discrimination threshold and plural detection (e.g., Simpson et al, 2005;Wolfe et al, 2010;Wolfe et al, 2011;Wolfe et al, 2015;Glista et al, 2009;Glista et al, 2012;Alexander et al, 2014;Hopkins et al, 2014;Zhang et al, 2014;Picou et al, 2015;Ellis and Munro, 2015). The difference in outcomes for the final vs medial /s/ in this study (VCV context vs /iC/ context) may be attributed to nonspectral cues that can help distinguish it from the final / Ð /, such as duration and intensity (e.g., Jongman et al, 2000), with the latter being longer and louder.…”
Section: Discussionsupporting
confidence: 91%
“…The available data suggests that the effect of context might depend on the severity of loss and consequently on the need for additional information beyond that provided by contextual cues. Testing listeners with mild to moderate SNHL, both Wolfe et al (2015) and Picou et al (2015) found improvements in /s/ discrimination by children and adults, respectively, following $1-month trial periods with NFC-enabled hearing aids, but found no statistical improvements on tests of speech recognition in noise. On the other hand, Wolfe et al (2011) reported improvements on both consonant recognition and sentence recognition in noise for children with moderate SNHL after 6 months of regular use of hearing aids with NFC, whereas early testing at 6 weeks did not show a significant difference for the sentence recognition task (Wolfe et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Findings are mixed on the effect of NFC relative to RBW on speech recognition and potential relationships are complex (Alexander, 2013; Alexander et al, 2014; Arehart et al, 2013; Bentler et al, 2014; Ching et al, 2013; Ellis & Munro, 2015; Glista et al, 2009; Glista et al, 2012; Hopkins et al, 2014; John et al, 2014; Kokx-Ryan et al, 2015; McCreery et al, 2013, 2014; Picou et al, 2015; Simpson et al, 2005, 2006; Souza et al, 2013; Wolfe et al, 2010, 2011, 2015). In general, benefit from NFC is better when access to high frequency sounds is increased with NFC (McCreery et al, 2013, 2014) but spectral distortion is minimized (Souza et al, 2013) as well as in listeners with greater high-frequency hearing loss (Brennan et al, 2014; Glista et al, 2009; Souza et al, 2013; but see Kokx-Ryan et al, 2015).…”
Section: Speech Recognitionmentioning
confidence: 99%